Using Concept Mapping as a Quality Learning Strategy for Engineering and ICT Undergraduates: An Exploratory Study - Wong, William Teck Foo; Lee, Justin Liak Yew
The evolution of holistic education arouses some pertinent questions of the validity and quality of learning, especially in the delivery of education in technical fields such as engineering and information and communications technology (ICT) which involves spatial and interconnecting ideas. A confronting fact is institutions of higher learning (IHLs) today are facing an uphill task in multiple attempts to wholesomely educate the generation Y. Born between the years of 1980 to 2000, their lives have been largely shaped by visual cues of globalization, multiculturalism, terrorism, and heroism rather than textual-based teaching-learning styles of yesterday years. This paper aims to review some of the previous research findings pertinent to these areas of interest. It also intends to present an exploratory research work that is being conducted based on phenomenology approach of the German philosopher Edmund Husserl (1859 – 1938) to study the use of concept mapping as a strategies instructional and assessment tool for learners in the fields of engineering and ICT.